Efficacy of the PEN-FAST score in a French cohort of patients with reported allergy to penicillins - Hanniet, Anatole; Puyraveau, Marc; Castelain, Florence; Pelletier, Fabien; Aubin, François (Frontiers in Allergy, 2024)
IntroductionVarious clinical decision-making tools for penicillin allergy have been developed to guide delabeling strategies.ObjectiveTo evaluate the penicillin allergy PEN-FAST decision score in a retrospective cohort of patients, adults and children, with penicillin-reported allergy.MethodsThis monocentric retrospective cohort included patients with penicillin-reported allergy. All patients underwent penicillin allergy testing using skin tests and/or drug challenge. The PEN-FAST score sensitivity, specificity, negative (NPV) and positive (PPV) predictive values, and the area under the receiver operating characteristics curve (AUC) were calculated.ResultsTwo hundred and fourteen patients were included (64 children and 150 adults). Allergy was confirmed in 52 cases (24%). A PEN-FAST score <3 points showed a poor discrimination capacity for the whole population (AUC = 0.66; 95% CI: 0.58–0.75), while it demonstrated a better discrimination capacity in the adults group (AUC = 0.71; 95% CI: 0.63–0.80). The sensitivity to identify penicillin allergy using this cutoff of less than 3 points was 0.67 (95% CI: 0.52–0.80); specificity, 0.58 (95% CI: 0.48–0.68); PPV, 0.43 (95% CI: 0.32–0.55); and NPV, 0.78 (95% CI: 0.68–0.87).ConclusionsAlthough our data confirm a rather good discrimination value of a PEN-FAST score <3 points, its low negative predictive value (78%) did not advocate for its use as an accurate, simple and cost-effective clinical decision-making tool to effectively reduce the number of penicillin skin tests required before direct oral challenge. Further studies are required to improve the predictive capacity of the PEN-FAST score.